The acquisition of English grammar and phonology by Cantonese ESL learners : challenges, causes and pedagogical insights - Chan, Alice Yin Wa (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Chan's exploration of the acquisition of English grammar and phonology by Cantonese learners of English as a Second Language (ESL) offers insights into the specific challenges that learners often encounter, and their origins, and posits ways to help them overcome the challenges. Possible sources of the challenges are also examined. The content covers the basic differences between English and Cantonese grammar as well as those between English and Cantonese phonology. Chan discusses the kinds of grammatical and phonological problems that Cantonese ESL learners often have in their acquisition of English. In terms of grammar, various structures are reviewed, including errors which are clearly due to L1 interference and also those which may not be directly L1-related. Learners' common misconceptions about relevant concepts are also revealed. In terms of phonology, both speech perception and speech production problems at the segmental and supra-segmental levels are examined. For learner problems which may be the result of L1 interference, a contrastive approach is adopted in analysing the cause and nature of the errors. Chan also offers readers pedagogical insights to target common grammatical problems, including the use of an algorithmic approach, the use of a discovery-based consciousness-raising approach, and the use of metalinguistic explanations. As far as the learning of English phonology is concerned, she argues that the training of speech production should go hand-in-hand with that of speech perception. Future research can experiment with the proposed teaching ideas with Cantonese ESL learners and learners of other native languages. Researchers and ESL teaching professionals will find the insights and research contained within this volume invaluable when encountering or researching Chinese ESL learners"--
Introduction -- English and Cantonese grammar in contrast -- English and Cantonese phonology in contrast -- Learner problems in the acquisition of English grammar I: interlingual errors -- Learner problems in the acquisition of English grammar II: English article errors -- Learner problems in the acquisition of English grammar III: other errors -- Learner problems in the acquisition of English phonology I: speech production -- Learner problems in the acquisition of English phonology II: speech perception -- Cantonese ESL learners' acquisition of grammar and phonology: L1 influence? -- The teaching of grammar to Cantonese ESL learners -- The teaching of phonology to Cantonese ESL learners -- Conclusions: the way forward.
Keywords: English language -- Study and teaching -- Cantonese speakers; English language -- Grammar -- Study and teaching; English language -- Phonology -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Phonetics & Phonics; FOREIGN LANGUAGE STUDY / English as a Second Language; LANGUAGE ARTS & DISCIPLINES / Grammar